The pet-sitting peril - Roberts, Willo Davis (New York : Aladdin Books ; London : Collier Macmillan, 1990)
A boy who does odd jobs in an apartment house becomes involved with a gang of arsonists employed by the building's owner, who plans to destroy it in order to collect the insurance.
Keywords: Arson; Detective and mystery stories; Apartment houses